Early Marriage Education at Islamic High School of Nahdlatul Wathan Keruak, Keruak District - Umar Bakri; Rijnan Rijnan; Muhamad Zaril Gapari; Nur Cahyani Ibnu Mariam S. (LP2M STIT Palapa Nusantara, 2025)
Early marriage, which reflects the low social status of women, remains a persistent social tradition that extends the childbearing period faced by adolescent brides and increases childbirth risks because they are not yet physically ready to give birth. This study aims to examine the implementation of early marriage education at MA NW Keruak and its impact on students’ awareness and behavior regarding early marriage. A qualitative method was employed, with data collected through interviews, observation, and documentation. The findings show that MA NW Keruak implements early marriage education through counseling, discussions, and extracurricular activities, thereby embedding the topic within both formal and non-formal school contexts. This education has a positive impact on students’ awareness of the risks and consequences of early marriage. The study concludes that integrating early marriage education into school programs constitutes a strategic effort to strengthen adolescents’ understanding of early marriage and is expected to serve as a reference for other schools in designing similar educational initiatives to help reduce the incidence of early marriage.